Food-related quality of life is impaired in inflammatory bowel disease and associated with reduced intake of key nutrients. Issue 4 (1st March 2021) - Whelan, Kevin; Murrells, Trevor; Morgan, Myfanwy; Cummings, Fraser; Stansfield, Catherine; Todd, Anne; Sebastian, Shaji; Lobo, Alan; Lomer, Miranda C E; Lindsay, James O; Czuber-Dochan, Wladyslawa
ABSTRACT: Background: Inflammatory bowel disease (IBD) may impact the extent to which food, eating, and drinking bring satisfaction and enjoyment to peoples' lives, and this may impact dietary intake. The prevalence of an impaired food-related quality of life (FR-QoL), its associated factors, and its impact on diet have not been explored. Objectives: To measure the prevalence and nature of the burden of impaired FR-QoL in people with IBD, the factors associated with these, and their associations with nutrient intake. Methods: We recruited 1576 outpatients with IBD (≥16 years old) in person from 7 IBD centers across the United Kingdom. Patients completed validated questionnaires to measure their FR-QoL, quality of life (QoL), distress, fatigue, anxiety, and depression. Dietary intake was recorded using the European Prospective Investigation into Cancer FFQ. A health professional recorded disease activity, Montreal classification, blood results, BMI, and malnutrition risk. FR-QoL was regressed onto explanatory variables using univariable and multivariable analyses. Results: Data from 1221 patients were available (77.4% response; Crohn's disease, 65%; ulcerative colitis, 35%). The FR-QoL mean (± SD) score was 80.8 ± 26.9, with wide ranges (minimum, 29; maximum, 145). Following multivariable regression, the strongest associations with FR-QoL were the number of recent disease flares (5 flares β = −12.7; P  < 0.001), the IBD-specific QoL (β = 0.33; P  < 0.001), and IBD-related distress (β = −0.26; P  < 0.001). Patients with poorer FR-QoL had lower intakes of fiber (nonstarch polysaccharide; Q1 to Q5 difference = 2.1 g/d; 95% CI: 0.4–3.8; P  = 0.048), calcium (192.6 mg/d; 95% CI: 112.5–272.6; P  < 0.001), phosphorus (167 mg/d; 95% CI: 58–276; P  = 0.041), and magnesium (34.4 mg/d; 95% CI: 9.3–59.4; P  = 0.041). Conclusions: Impaired FR-QoL is prevalent in IBD and is associated with recurrent disease flares, a reduced IBD-specific QoL, and greater IBD-related distress. A poorer FR-QoL was associated with lower intakes of key nutrients of importance to IBD, including those relating to gut health and bone mineralization.